Clinical practice guidelines for the diagnosis and management of skin and soft tissue infections in Colombia (2019)
Skin and soft tissue infections (SSTI) represent the third leading cause of infectious disease consultation for medical services after respiratory and urinary tract infections. This document generates a clinical practice guideline with 38 recommendations based on evidence, graduated under the SIGN system for the diagnosis and treatment for SSTI infections in adult patients in Colombia, following a process of adaptation of guidelines published, and the systematic search and synthesis of literature for the updating of scientific evidence. In addition, a consensus of experts was made for the evaluation of the potential barriers for the implementation of the recommendations and the evaluation of the degree of recommendation in the local context. © 2019 Asociacion Colombiana de Infectologia. All rights reserved.